Guidance on managing environmental risks associated with land contamination at filling stations. (Energy Institute, 2018)
The intent of this publication is to act as a reference guide for individuals charged with the management of environmental risks associated with land and groundwater contamination at filling stations and to direct them to relevant legislation, codes of practice and other publications. It provides information to help site operators: make informed judgements about environmental risks associated with land contamination at their sites; monitor and review the activities related to land contamination carried out by consultants/contractors working on their behalf; understand the relevance of land contamination to redevelopment plans or acquisitions/disposals, and hold effective discussions with regulatory authorities on land contamination issues. This publication supersedes the former Energy Institute (EI) publication Guidelines for the investigation and remediation of petroleum retail sites, providing updates in the context of the current UK framework concerning contamination of land and groundwater.
"July 2018"
Keywords: Petroleum -- Underground storage -- Environmental aspects -- Great Britain.; Service stations -- Environmental aspects -- Great Britain.; elektronické knihy; electronic books